ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT FINANCIAL DISTRESS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI TAHUN 2010-2014 - Mayang Murni (Universitas Medan Area, 2018)
The objective of the research was to examine the influence of size, firm age, CR, DER, ROA, ROE, NPM, EPS, and PER on financial distress level with. The population was manufacture companies listed in BEI (the Indonesia Stock Exchange) in the period of 2010-2014. The samples were 73 manufacture companies listed in BEI, taken by using purposive sampling technique so that there were 365 observations. The data were secondary data which were obtained from financial statement. The gathered data were analyzed by using multiple linear regression analysis and path analysis with an SPSS 21 software program. The result of the research showed that ROA had negative and significant influence on financial distress level. Firm size, Current Ratio, DER, ROE, EPS, and PER had negative and insignificant influence on financial distress level. Meanwhile, firm age had positive but insignificant influence on financial distress level, and NPM had positive and significant influence on financial distress level.